SEMA: An Approach Based on Internal Measurement to Evaluate Energy Efficiency of Android Applications - Fischer, Leonardo Matthis; Brisolara, Lisane Brisolara de; Mattos, Júlio Carlos Balzano De (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2015)
This work proposes an approach for energy consumption estimation of Android applications based on internal measurement. The proposed approach uses samples of voltage and current extracted from the battery of the Android device driver itself. This approach is able to measure the energy consumption of an Android application, or parts of its code. Experiments demonstrate the proposal and compare its results to those obtained by an external measurement approach and a model based approach. Experimental results demonstrate that the proposed approach can achieve consistent results compared to other approaches and presents advantages as low granularity, easy-to-use and low overhead.